Financing infrastructure projects : a practical guide - Merna, Tony; Al-Thani, Faisal F. (ICE Publishing, 2018)
Finance is a necessity for all public or private sector projects. Over the past 20 years, the private sector has increasingly financed projects traditionally considered in the public domain. This title discusses the subject.